2020
DOI: 10.12688/wellcomeopenres.15873.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Staphylococcus aureus infection and other outcomes between users of angiotensin-converting-enzyme inhibitors and angiotensin II receptor blockers: lessons for COVID-19 from a nationwide cohort study

Abstract: Background: Mice receiving angiotensin converting enzyme inhibitor (ACEI) drugs show increased susceptibility to infection by Staphylococcus aureus (S. aureus). We sought to investigate whether humans using ACEI were at increased risk of S. aureus infection, comparing them to users of Angiotensin II Receptor Blockers (ARB) with multiple control outcomes to assess the potential for residual confounding. Methods: Using the UK Clinical Practice Research Datalink linked to Hospital Episode Statistics between 1997 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, recent studies in humans have identified no difference in ACE2 levels following exposure to ACE or ARB use (Emilsson et al 2020); (Gill et al 2020). Therefore, our findings could also be explained by residual confounding, as suggested by recent comparisons of the incidence of Staphylococcus aureus infection and other outcomes between ACE and ARB use which suggest that ARB is not a perfect comparator for ACE, although no large scale PS-adjustment was used (Bidulka et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…However, recent studies in humans have identified no difference in ACE2 levels following exposure to ACE or ARB use (Emilsson et al 2020); (Gill et al 2020). Therefore, our findings could also be explained by residual confounding, as suggested by recent comparisons of the incidence of Staphylococcus aureus infection and other outcomes between ACE and ARB use which suggest that ARB is not a perfect comparator for ACE, although no large scale PS-adjustment was used (Bidulka et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“… 49 , 50 , 51 Therefore, our findings could also be explained by residual confounding, as suggested by recent comparisons of the incidence of Staphylococcus aureus infection and other outcomes between ACEI and ARB use, which suggest that ARB use is not a perfect comparator for ACEI use, although no large-scale propensity score adjustment was used. 52 …”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Therefore, our findings could also be explained by residual confounding, as suggested by recent comparisons of the incidence of Staphylococcus aureus infection and other outcomes between ACEI and ARB use, which suggest that ARB use is not a perfect comparator for ACEI use, although no large-scale propensity score adjustment was used. 52 Furthermore, one study has reported an increased risk of hospital admission with COVID-19 and intensive care unit admission associated with use of ACEIs and ARBs. 43 Although we did not observe a consistent increased risk of hospital admission with COVID-19, we did observe an increased risk of hospital admission with pneumonia, acute respiratory distress syndrome, acute kidney injury, or sepsis largely driven by ACEI use compared with CCB or THZ use.…”
Section: Discussionmentioning
confidence: 99%
“…or ARBs, the use of ACE-Inhs. was associated with increased rates of S. Aerus and gram-negative infections, while herpes zoster was more commonly associated with ARBs ( Bidulka et al, 2020 ). In addition, the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%